System mierników sieci dostaw - Rodawski, Bartłomiej (Supply Net Metrics, 2005)
The purpose of the paper is to present framework for supply net metrics setting. The author introduces three level metrics system, and proposes the examples of strategic metrics (level 1). Moreover two concepts of establishing process (level 2) and functional metrics (level 3) are described: balanced score card and supply chain reference model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 147-157